2021
DOI: 10.1002/1348-9585.12266
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of working hours and chronic kidney disease in healthy workers: The Kangbuk Samsung Health Study

Abstract: Objectives Long working hours are linked to an increased risk of exposure to work safety hazards that threaten the health of workers. To date, only a few cross‐sectional studies regarding the relationship between working characteristics, such as over‐workload and chronic kidney disease (CKD) have been reported. Therefore, in this longitudinal study, we aimed to examine the direct relationship between long working hours and the incidence of CKD. Methods We included 97 85… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
0
10
1
Order By: Relevance
“…The Institutional Review Board of Kangbuk Samsung Hospital approved this study (approval number: KBSMC 2022-03-011) and waived the requirement for informed consent because we only used de-identified data obtained as part of routine health screening examinations 13 , 16 . All methods of the study were performed in accordance with the relevant guidelines and regulations including Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Institutional Review Board of Kangbuk Samsung Hospital approved this study (approval number: KBSMC 2022-03-011) and waived the requirement for informed consent because we only used de-identified data obtained as part of routine health screening examinations 13 , 16 . All methods of the study were performed in accordance with the relevant guidelines and regulations including Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…Smoking status was categorized as never smoked, former smoker, or current smoker 15 . Regular exercise refers to exercising three or more times per week 16 . Education level was divided into non-collegiate education and a college graduate 16 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A cohort study found a significant association between long working hours (>52 hours) and the incidence of CKD. However, further efforts are needed to study the underlying mechanism of this association [30]. Almost 50% of CKD patients have insomnia or impaired sleep quality [31].…”
Section: Stress Working Hours and Sleepmentioning
confidence: 99%
“…2018), kidney (Lee et al . 2021) and cardiovascular disease (Torquati et al . 2018), as well as hypertension (Makarem et al 2021), compared to people who work day shifts.…”
Section: The Unrelenting Presence Of Insufficient Sleep In Shift Workersmentioning
confidence: 99%